Corneal neovascularization associated with rigid contact lens wear in patient with keratoconus: a case report - Galgauskas, Saulius; Valatkienė, Ignė (Lietuvos chirurgija, 2017)
Contact lenses are perfect choice in order you live an active life and you do not want to wear glasses. As long as contact lenses are very comfortable to wear, they could cause some issues. People who wear contact lens, do not always follow recommendations their doctor gave, they also do not wear them properly. In addition to this, some of the eye conditions and diseases may also initiate the beginning of the development of contact lens related noninfectious complications. The case report of an adult man with keratoconus is presented in this article. Rigid contact lenses are recommended in order to ensure good vision. However, they can be the reason initiating the development of noninfectious contact lens complications, in this case – corneal neovascularization. In this article the evidence-based information about keratoconus and corneal neovascularization treatment options and prevention is presented.
Keywords: cornea; keratoconus; corneal neovascularization; contact lens